An implementation of X.25 over TCP/IP : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Computing Technology at Massey University - Rasiah, Ajitkumar JW (Massey University, 1991)
Computer Networks are being used increasingly around the world. More importantly, many of these networks are interconnected by gateways, allowing a user in one geographical location to send and receive messages from a host located elsewhere. The International Standards Organisation (ISO) has proposed the Open Systems Interconnection (OSI) Reference Model as a basis for building computer networks and the protocols which are used on those networks. Developers of networks are encouraged to follow these guidelines so that their networks may have an 'open architecture'. This thesis examines two networking protocols, CCITT's X.25 Recommendation and TCP/IP. It continuously refers back to the OSI Reference Model as it describes the design of these protocols. It then looks at an implementation of X.25 over TCP/IP, which will allow users on non-X.25 hosts to develop and run X.25 applications courtesy of a separate host that supports X.25.
Keywords: Computer networks; Computer network protocols